Potential Biomarkers and Inflammatory Modulation of Hyperbaric Oxygen Therapy in Long COVID: A Narrative Update - Soedarsono Soedarsono; Rike Andy Wijaya; Verna Biutifasari (Jurnal Respirasi, 2026)
Introduction: Long coronavirus disease (COVID-19), also known as post-acute sequelae of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (PASC), is characterized by persistent, often debilitating symptoms that extend beyond the acute phase of COVID-19. These manifestations are associated with immune dysregulation, chronic inflammation, and oxidative stress. Hyperbaric oxygen therapy (HBOT), which involves inhaling 100% oxygen at elevated atmospheric pressure, has emerged as a potential intervention to mitigate these processes. This narrative review synthesized findings from recent clinical and translational studies evaluating the immunological effects of HBOT in patients with long COVID. Methods: A structured search of PubMed, Scopus, and ScienceDirect was conducted for articles published between January 2020 and April 2025 using predefined keywords related to HBOT, long COVID, inflammation, and biomarkers. Seven primary studies met the inclusion criteria and were analyzed for their clinical outcomes and molecular immunomodulatory effects. Results: Evidence indicates that HBOT contributes to significant reductions in pro-inflammatory cytokines, such as interleukin (IL)-6 and tumor necrosis factor-α (TNF-α), while increasing anti-inflammatory cytokines, such as IL-10. Improvements in systemic biomarkers, including C-reactive protein, ferritin, and reactive oxygen species (ROS), have also been observed. In parallel, HBOT has been linked to enhanced mitochondrial function, immune balance, and tissue oxygenation, all of which support recovery from long COVID-related organ dysfunction. Conclusion: Despite promising results, heterogeneity in study design, small sample sizes, and limited long-term follow-up highlighted the need for further rigorous, standardized clinical trials. Overall, HBOT appears to be a biologically plausible and clinically relevant adjunctive therapy for long COVID, with inflammation-related biomarkers serving as correlates or secondary indicators of therapeutic response.